Growth of Molybdenum Carbide–Graphene Hybrids from Molybdenum Disulfide Atomic Layer Template. Issue 4 (27th January 2017) - Wu, Jingjie; Ma, Lulu; Samanta, Atanu; Liu, Mingjie; Li, Bo; Yang, Yingchao; Yuan, Jiangtan; Zhang, Jing; Gong, Yongji; Lou, Jun; Vajtai, Robert; Yakobson, Boris; et al.
Abstract : Molybdenum carbide–graphene hybrid constituting few‐layer graphene and molybdenum carbide nanoparticles is synthesized by carburizing molybdenum disulfide atomic layer substrate. At the elevated temperature and reducing environment, molybdenum disulfide is reduced to molybdenum acting as the catalyst for graphene growth, while simultaneously molybdenum atoms are carburized to form molybdenum carbide. This hybrid has potential applications in heterogeneous catalysis.